Implementasi Isbat Nikah Massal Di Madura: Kajian Sosiologis-Filosofis - Muh. Fathoni Hasyim (State Islamic University (UIN) of Sunan Ampel, 2019)
Marriage is a very important and sacred event in married life. Marriage is a legitimate starting point to establish kinship and brotherhood of the two extended families. So, it’s not uncommon for a wedding to be enlivened by a lively party, spending a very large budget. Nevertheless, there is a certain community in Madura that ignores it, so it does not record it in the official institution, the KUA (the Office of Religious Affairs). Even though marriage registration brings benefit, justice and protection of civil rights as well as preventive measures in preventing unawareness, so that the MWC NU of Gapura, Sumenep runs a program called “Mass Isbat Nikah”. The above problems raise two questions. Why do many isbat of marriage occur in a married couple? and how is the implementation? The review of this article will focus on how the implementation of mass marital marriage in Madura with socio-philosophical analysis.